Výskyt nesteroidních antiflogistik ve vodním prostředí a jejich účinky na vodní organismy - Láníková, Jana; Blahová, Jana; Svobodová, Zdeňka (Chemické listy, 2021)
Non-steroidal anti-inflammatory drugs (NSAIDs) are drugs with analgesic, antipyretic and anti-inflammatory effects. They are widely used in human and veterinary medicine. The most used NSAIDs include ibuprofen, diclofenac, naproxen and ketoprofen. Due to their excessive use and insufficient disposal in wastewater treatment plants, through which the active substances of medicinal products, their degradation products and metabolites can pass, surface water pollution occurs. This fact may have a negative impact on aquatic organisms. It was found that non-steroidal anti-inflammatory drugs can in increased concentration cause oxidative stress, damage to the liver, gills and kidneys and cause reproductive disorders in fish. They also negatively affect aquatic invertebrates, representatives of producers (phytoplankton) and destruents (bacteria), in which they have an inhibitory effect on growth and reproduction. The present review summarizes the existing knowledge regarding the occurrence of non-steroidal anti-inflammatory drugs in the aquatic environment and their effects on aquatic organisms.